2008
DOI: 10.1577/m06-146.1
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Radio Wave Transmission and Reception: Use of Radiotelemetry in Large River Systems

Abstract: Many technical and environmental variables affect radio wave transmission and reception in aquatic environments. We used a controlled experimental design in three large North American rivers (Illinois and Mississippi rivers, Illinois, and Skeena River, British Columbia) to examine the effects of water conductivity, transmitter depth, electromagnetic noise, antenna height, and transmitter type on detection distance. Detection distance was significantly affected by water conductivity, transmitter depth, and elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 6 publications
1
20
0
Order By: Relevance
“…Flatbed PIT antennas reasonably robust to ice processes [32] In small streams, use mobile PIT antennas through the ice [ Can use CART tags [22] A downrigger device has been developed that enables tracking of radio-tagged fish at depth, but has limited reception zone [37] Low-frequency radio tags can improve performance in deep water [35] as can use of more powerful batteries or stronger transmitter output [36] Abiotic Thermocline Thermoclines can impair the performance of acoustic transmitters [38,39], but radio transmitters are unaffected (aside from the fact that thermoclines often occur at depth)…”
Section: Stationary Trackingmentioning
confidence: 99%
“…Flatbed PIT antennas reasonably robust to ice processes [32] In small streams, use mobile PIT antennas through the ice [ Can use CART tags [22] A downrigger device has been developed that enables tracking of radio-tagged fish at depth, but has limited reception zone [37] Low-frequency radio tags can improve performance in deep water [35] as can use of more powerful batteries or stronger transmitter output [36] Abiotic Thermocline Thermoclines can impair the performance of acoustic transmitters [38,39], but radio transmitters are unaffected (aside from the fact that thermoclines often occur at depth)…”
Section: Stationary Trackingmentioning
confidence: 99%
“…Radio transmitters have conductivity restrictions, but the signals should be clear in relatively shallow water (< 4 m) with conductivity < 800 μS/cm, but become less detectable after this conductivity threshold is reached (Peters et al 2008). Measurements taken in February 2007 about 1.25 km upstream of the Río Cañas mouth indicated that conductivities were acceptable for radio signal transmission (583 μS/cm; C. Mace, Mississippi State University, unpublished data).…”
Section: Radio Telemetrymentioning
confidence: 99%
“…The distance of the transmitted signal through water and water conductivity are paramount when determining expected range for radio telemetry (Eiler, 1990;Freund and Hartman, 2002) and detection distance exponentially decreases with increased distance that a signal must travel through water (Peters et al, 2008). Another consideration for employing underwater radio antennas, is the ease of creation.…”
Section: Applications and Improvementsmentioning
confidence: 99%
“…Niemela et al, 1993;Martinelli and Shively, 1997;Brown et al, 2006); however, there are only a few applications of underwater radio antennas mentioned in the primary literature (e.g., Bunt et al, 2003;Beeman et al, 2004;Brown et al, 2006;Peters et al, 2008). This paucity of information on underwater radio antennas necessitates further research on antenna design and understanding (Beeman et al, 2004), since many useful applications exist in the study of aquatic organisms.…”
Section: Introductionmentioning
confidence: 99%